Pomocniczość jako zasada udziału podmiotów niepublicznych w realizacji zadań administracji publicznej - Wilczyński, Przemysław (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The presence of non-public entities in the domain of public administration, to this day, has not been supported by either a coherent concept within the theory of law for the participation of non-public entities in the undertakings of public administration or in consistent legal solutions devised with such participation in mind. However, since 1997 this presence has been enjoying its constitutional backing in the subsidiarity principle in the Preamble to the Constitution. The subsidiarity principle, perceived as a moral principle, or the foundation for building the rules of public governance, or a legal principle, dictates mutual relations between individuals and various forms of public life. By influencing the shape of public administration, among other things, it also defines the position of non-public entities towards state organs in a broad sense, and towards other non-public entities operating under the legal governance of the state. It can also be seen as the rule implying the participation of non-public entities in the undertakings of public administration. Dissertations in this paper focus on subsidiarity – that is the basis and the principle of participation of non-public entities in the undertakings of public administration.